Новые и малоизвестные виды мицетофилоидных двукрылых (Diptera, Mycetophiloidea) фауны СССР - Зайцев, А.И. (Вестник зоологии, 1982)
Three new species -Allodiopsis korolevi sp. n., A. adumbrata sp. n. and Pseudexechia ussuriensis sp. n. - are described. From closely related species they differ by the male genitaliastructure. Symmerus antennalis O k a d a, Diadocidia valida M i k , Allodiopsis rustica (E d w.) for the first time are shown for the USSR territory. Distributional data
for all the species are given.